Literature Review: The Role of Balanced Nutrition in Improving Body Immunity During the Pandemic - Firayani, Firayani (Journal Nutrizione, 2025)
The COVID-19 pandemic has raised global awareness of the importance of a strong immune system as the body's primary defense against infection. One of the key factors that influences immunity is a balanced nutritious diet. This study uses a qualitative approach with a literature study method to analyze the role of balanced nutrition in improving immunity during the pandemic. The results of the study show that macronutrients such as protein and micronutrients such as vitamins A, C, D, E, and minerals such as zinc and selenium have a significant contribution to supporting the immune system. Deficiency of any one of these nutrients has been shown to weaken the immune response and increase the risk of infection. On the other hand, many people still do not understand the principles of balanced nutrition as a whole, resulting in erroneous consumption practices, such as relying on supplements without paying attention to holistic diets. In addition, disinformation during the pandemic has exacerbated the gap in public nutritional knowledge. Therefore, education based on scientific evidence is very important to build a correct understanding of the role of nutrition in maintaining immunity. The results of this study are expected to be a reference in formulating strategies to improve public health through a sustainable nutritional approach